PENGEMBANGAN MEDIA GAMIFIKASI QUIZIZZ INDONESIAKU KAYA RAYA PEMBELAJARAN IPAS PADA SISWA KELAS V - Hayina Putri Permatasari; Dewi, Galuh Kartika; Susilo, Tri Ahmad Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the fact that interactive learning media has not been used in IPAS (Social and Natural Sciences) learning in class V. In this case the teacher has not used digital learning media which can cause students to feel bored and lack of enthusiasm during IPAS learning, ultimately having an impact on student learning outcomes that are not optimal. The purpose of this research is to develop quizizz gamification learning media, to determine student learning outcomes and student responses to quizizz media. Quizizz is software in the form of a quiz game that aims to build interactive learning interactions and improve student learning outcomes. In this study, the author chose the Research and Development (R&D) method, because this method is often used to produce new products or improve existing products. This research model is 4D. The 4D model stands for Define, Design, Development and Dissemination, with data collection techniques in the form of validation sheets, tests and questionnaires. The final results obtained from this study are very valid with a score of 92% media experts and 96% material experts and obtained the final result of validation which is 94% with very feasible criteria. Student learning outcomes after using quiziz gamification learning media increased by 30.1 where before using quizizz the average student score was 61.33 to 91.43 after using quizizz learning media. And student responses in using quiziz gamification media are very satisfying with an average score of 93%.